Mazhab Tafsir Periode Modern-Kontemporer: Sumber, Metode, Corak, dan Tokoh mufassir - Iqbal Ilmi; Serlyana Yuriska; Akhmad Dasuki (JURNAL ILMIAH NUSANTARA, 2025)
This article examines the development of Qur'anic exegesis schools during the modern-contemporary period in Indonesia, focusing on the sources, methods, interpretive approaches, and influential exegetes. The study employs a qualitative, descriptive-analytical method based on library research. The findings indicate that Qur'anic interpretation in modern Indonesia has evolved from a strictly textual approach to one that is more contextual and rational. The sources of interpretation include both tafsir bi al-ma’tsur (tradition-based) and tafsir bi al-ra’yi (reason-based), while the methods applied range from ijmali (global), tahlili (analytical), and muqaran (comparative) to maudhu’i (thematic), with the thematic method being predominant in addressing contemporary issues. The interpretive trends that have emerged include mystical (sufi), jurisprudential (fiqhi), philosophical (falsafi), scientific (ilmi), and socio-literary (adabi ijtima’i) approaches. This study also highlights the contributions of three prominent Indonesian exegetes: A. Hasan with Tafsir al-Furqan, Hasbi Ash-Shiddieqy with Tafsir An-Nur, and Hamka with Tafsir al-Azhar. Each scholar demonstrates a unique methodological orientation shaped by their respective social, educational, and historical contexts. The study underscores the importance of dynamic, scholarly, and contextual approaches to Qur'anic interpretation to ensure its relevance in contemporary Muslim life.